Preparation of Nanoliposomes by Size Exclusion Chromatography to Entrap Soluble Antigens from Leishmania Donovani - Abdallah , Rawaa N.; Allihaibi , Raghad K.; Al-Halbosiy, Mohammad M.F.; Taha, Ali A. (Iraqi Journal of Science, 2022)
In this study, we investigated the ability of nanoliposomes preparation, as a nanoadjuvant, to entrap soluble Leismania donovani antigens (SLAs) and release in vitro. The parasite reactivation was carried out when inoculated into Rosewell park memorial institute media (RPMI) and incubated at 23 °C for 4 days. L. donovani promastigote inoculum (104 cell / ml) of 4 days was used to inoculate modified medium of Saline - Neopeptone and Blood agar 9 (SNB 9) to produce promastigote mass. SLAs were extracted from the promastigotes ghost membrane after fourth passages of subculturing in SNB. The membrane pellet obtained was suspended in 5 mM Tris buffer (pH 7.6) and sonicated three times at 4 °C and entrapped in freshly prepared nanoliposomes. Lipids mixture of 4mM Phosphatidylcholine, 2.2 mM Cholesterol and 0.55 mM Phosphatidylethanolamine in a ratio of 7:2:1 were used to prepare nanoliposome. Physio-chemical characterizations of prepared nanoliposomes was performed by using Scanning Electron Microscope (SEM) , Atomic Force Microscope (AFM) and Zeta Potential assays to determine the size, morphology and charge. The efficiency of freshly prepared nanoliposoms to entrap SLAs was determined by measuring the nanoliposome efficiency entrapment (EE). The percentage of EE was 50 and 27.5 of SLAs entrapped nanoliposomes prepared by Sephadex G25 and Sephadex G75, respectively. Moreover, stability of SLAs entrapped nanoliposomes was examined at 4 and 37 °C as a storage temperature.